Highly adhesive dendritic branched polymer and its synthesis method and application

By performing multiple anionic polymerization reactions under anhydrous and oxygen-free conditions, combining structural regulators and halogen-containing styrene compounds, a highly adhesion dendritic branched polymer was prepared, which solved the problem of existing polymers affecting the flow of polymer chains when improving adhesion, and achieved excellent adhesion performance and convenience of industrial production.

CN116410426BActive Publication Date: 2025-03-11PETROCHINA CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111644459.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-29
Publication Date
2025-03-11
Estimated Expiration
2041-12-29

AI Technical Summary

Technical Problem

When existing polymers improve adhesion, they often affect the viscosity flow of polymer chains or reduce the cohesion of polymers, making it difficult to achieve excellent adhesion properties.

Method used

Under anhydrous and oxygen-free conditions, anionic polymerization monomer is added to the organic solvent, and polymerization is initiated by initiating the polymerization with an initiator, structural regulators and halogen-containing styrene compounds are added, and the polymerization steps are repeated multiple times, and the terminator and anti-aging agent are finally added to prepare a highly adhesion dendritic branched polymer.

Benefits of technology

The synthesis of dendritic branched polymers with high adhesion properties has been achieved, and it has excellent adhesion properties. It is suitable for plastic or rubber blending, which significantly improves the adhesion properties of the polymers, and has mild operating conditions and is easy to produce in industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116410426B_ABST
    Figure CN116410426B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of polymer materials, synthesis methods and applications, and is a highly adhesive dendritic branched polymer, synthesis method and application. The highly adhesive dendritic branched polymer is prepared according to the following synthesis method: firstly, an anionic polymerization technology is used to synthesize polymer active chains, and a halogen-containing styrene compound and anionic polymerization monomer are added to the synthesized solution for multiple times to synthesize a highly adhesive dendritic branched polymer. The highly adhesive dendritic branched polymer synthesized by the present invention has excellent adhesion properties, can be used in plastic or rubber blending, and is beneficial to improving the adhesion properties of polymers. In addition, the method has mild operating conditions and is easy to industrialize; it can be directly used or added to other polymers, and can significantly improve the adhesion properties between objects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, synthesis methods and applications, and is a highly adhesive dendritic branched polymer and a synthesis method and application. Background Art

[0002] The adhesion of polymers is often used to characterize the ease of separation between polymers or between polymers and other objects. Good adhesion requires that the two molecules can achieve intermolecular contact, which requires that the polymer chains on the contact surface can flow viscously and achieve full contact. During separation, strong connecting bonds are required to prevent them from being easily separated. If the two objects in contact are polymer melts, full contact requires that the polymer chains can diffuse across the interface and entangle with each other. Usually, the strength of the polymer connecting bonds can be increased by adding reinforcing agents or cross-linking, but this will affect the viscous flow of the polymer chains and is not conducive to full contact between objects. The addition of plasticizers is conducive to full contact, but it will reduce the cohesive force of the polymer. Therefore, the development of branched polymers with high adhesion properties is of great significance for their adhesive applications.

[0003] Although the adhesion of polymers has many applications in life, the adhesion mechanism is still not very clear, such as crack diffusion mechanism, mechanical action and electrostatic action mechanism. Adhesion testing is mainly divided into two stages: the formation of the "connecting bond" (the contact stage between the probe and the pressure-sensitive adhesive) and the separation process (probe stretching and separation). There is a complex energy dissipation process in the whole process. Generally, the adhesion of a material is mainly related to the surface properties of the material, the viscoelasticity of the material and the external environment. When different materials are in contact, this adhesion behavior is called adhesion; and the same materials are in adhesive contact, which is called cohesion. In real life, we touch the adhesive material with our fingers and measure its adhesion performance by the movement of our fingers. In actual testing, the commonly used polymer adhesion test methods mainly include probe test, tear test and ball test. Probe test is one of the commonly used means to test polymer adhesion, which is convenient and efficient. It mainly uses the probe to make vertical contact with a sample of a certain thickness. After a period of contact, it is separated at a constant speed, and the separation curve is used to measure the adhesion performance of the material. Depending on the probe, the probe adhesion test can be divided into spherical and flat probe tests. The contact surface of a spherical probe is three-dimensional, and the contact surface between the probe and the sample does not need to be much larger than the thickness of the sample; while a flat probe requires the contact surface radius to be much larger than the sample thickness. Generally, the adhesion behavior of polymers tends to exhibit solid-like and liquid-like adhesion behaviors. In solid-like adhesion behavior, the stress often reaches its maximum value under very small strains, the adhesion energy is relatively small, and the separation mainly occurs at the interface between the probe and the polymer; while liquid-like adhesion behavior exhibits a lower maximum tensile force and a very high fracture strain, and the separation occurs between the polymers. After the stretching is completed, some polymer will remain on the probe. Summary of the invention

[0004] The present invention provides a highly adhesive dendritic branched polymer and a synthesis method and application thereof, which overcome the deficiencies of the above-mentioned prior art and can synthesize a branched polymer with excellent adhesion performance. The branched polymer has a dendritic structure, mild synthesis conditions, simple operation, and is easy for industrial production.

[0005] One of the technical solutions of the present invention is achieved by the following measures: A method for synthesizing a highly adhesive dendritic branched polymer comprises the following steps:

[0006] (1) under anhydrous and oxygen-free conditions, anionic polymerization monomers are added to an organic solvent, polymerization is initiated by an initiator, and a structure regulator is added to first prepare a polymer active chain;

[0007] (2) adding a small amount of halogen-containing styrene compound to the reaction solution of step (1), and adding anionic polymerization monomer again to continue polymerization;

[0008] (3) After the reaction is completed, step (2) is repeated multiple times, and finally a terminator and an antioxidant are added, and the precipitate is washed, filtered and vacuum dried to obtain a highly adhesive dendritic branched polymer.

[0009] The following is a further optimization and / or improvement of one of the above-mentioned technical solutions:

[0010] In the above step (1), the initiator may be alkyl lithium or alkali metal alkoxide or alkali metal amide or sodium naphthalene; the anionic polymerization monomer may be one or more of conjugated diene and benzene olefin derivatives; the initiator concentration is 0.01 mol / L to 10.00 mol / L,

[0011] Preferably, the initiator concentration is 0.01 mol / L to 2 mol / L.

[0012] The alkyl lithium is one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium and isobutyl lithium, and the alkali metal amide compound is sodium amide or lithium amide; the alkali metal amide compound can be a secondary amine compound reacting with an alkyl lithium initiator to form an amide lithium initiator, such as cycloheximide lithium initiator.

[0013] The structure regulator is 2,2-di(2-furyl)propane, and the amount of 2,2-di(2-furyl)propane added is 0.5 times the molar number of the initiator.

[0014] The conjugated dienes may be one or more of isoprene and butadiene; the phenyl olefin derivatives may be one or more of styrene and 1-phenyl-1,3-butadiene.

[0015] In the above step (1), the organic solvent is selected from one or more linear or cyclic organic solvents; the linear organic solvent is selected from one or more of n-hexane, pentane, heptane and octane; the cyclic organic solvent is selected from a long-chain molecular chain or epoxy hydrocarbon organic solvent, the long-chain molecular chain organic solvent is selected from one or more of cyclohexane, cyclopentane and cycloheptane, and the epoxy hydrocarbon organic solvent is selected from tetrahydrofuran.

[0016] In the above step (1), the conditions of the anionic polymerization reaction are to react at 10°C to 80°C for 1 minute to 400 minutes; at the same time, in the polymerization reaction liquid, the solid content of the anionic polymerization monomer does not exceed 50%, because as the solid content of the monomer in the reaction liquid increases, the danger caused by the thermal effect of the polymerization reaction increases.

[0017] In the above step (1), preferably, the anionic polymerization condition is 30° C. to 70° C., and the solid content of the anionic polymerization monomer in the polymerization reaction solution is 15%.

[0018] In the above step (2), the styrene compound containing a halogen element is one of 3-chlorostyrene, 2-bromostyrene, trans-4-bromostyrene, 4-bromostyrene, 2-chlorostyrene and 4-chloromethylstyrene.

[0019] Preferably, the molar ratio of the total amount of the halogen-containing styrene compound added to the amount of the initiator added is 0.1 to 10.

[0020] In the above step (3), the terminator is one of carbon dioxide, organic acid, water and isopropanol; the antioxidant is one or more of 2,6-di-tert-butylphenol, ketoamine antioxidants, diphenylamine derivatives, p-phenylenediamine derivatives, 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and phenol-free phosphite.

[0021] The amount of the antioxidant added is 1% to 2% of the mass of the high-adhesive dendritic branched polymer.

[0022] The second technical solution of the present invention is achieved by the following measures: a highly adhesive dendritic branched polymer prepared according to the method for synthesizing a highly adhesive dendritic branched polymer described in the first technical solution.

[0023] The third technical solution of the present invention is achieved by the following measures: application of the high-adhesion dendritic branched polymer described in the second technical solution in high-adhesion polymer materials.

[0024] The highly adhesive dendritic branched polymer synthesized by the present invention has excellent adhesive properties and can be used in plastic or rubber blending, which is beneficial to improving the adhesive properties of polymers. In addition, the method has mild operating conditions and is easy for industrial production; or it can be directly used or added to other polymers to significantly improve the bonding properties between objects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Attached Figure 1 Schematic diagram of the synthesis route for synthesizing branched polymer I in Example 1.

[0026] Attached Figure 2 This is the NMR spectrum of the branched polymer I synthesized in Example 1.

[0027] Attached Figure 3 This is the rheological diagram of the branched polymer I synthesized in Example 1.

[0028] Attached Figure 4 This is a graph showing the adhesion performance of the branched polymer I synthesized in Example 1.

[0029] Attached Figure 5 This is a structural diagram of the branched polymer I synthesized in Example 1.

[0030] Attached Figure 6 This is the NMR spectrum of the branched polymer II synthesized in Example 2.

[0031] Attached Figure 7 This is the rheological diagram of the branched polymer II synthesized in Example 2.

[0032] Attached Figure 8 This is a graph showing the adhesion performance of the branched polymer II synthesized in Example 2.

[0033] Attached Fig. 9 This is a structural diagram of the branched polymer II synthesized in Example 2.

[0034] Attached Fig.10 This is the rheological diagram of the branched polymer III synthesized in Example 3.

[0035] Figure 1 In the above, n-BuLi represents butyllithium.

[0036] In the rheological diagram, in the ordinate, G' represents the storage modulus and G" represents the loss modulus. DETAILED DESCRIPTION

[0037] The present invention is not limited by the following embodiments, and the specific implementation method can be determined according to the technical scheme of the present invention and the actual situation. Unless otherwise specified, the various chemical reagents and chemicals mentioned in the present invention are all chemical reagents and chemicals known and used in the prior art; unless otherwise specified, the percentages in the present invention are all mass percentages; unless otherwise specified, the solutions in the present invention are all aqueous solutions with water as the solvent, for example, hydrochloric acid solution is a hydrochloric acid aqueous solution; the room temperature in the present invention generally refers to a temperature of 15°C to 25°C, and is generally defined as 25°C.

[0038] The present invention will be further described below in conjunction with embodiments:

[0039] Example 1: The highly adhesive dendritic branched polymer was prepared by the following synthesis method:

[0040] In a 850ml reaction bottle pre-treated with nitrogen positive pressure, use a double-ended needle to introduce 400ml of n-hexane solution and 8ml of isoprene monomer, add 2.18ml of calibrated n-butyl lithium (molar concentration of 1mmol / ml) to initiate polymerization, and add 2,2-di(2-furyl)propane (structure regulator) corresponding to half the molar number of n-butyl lithium. After reacting in a 60℃ water bath for 2h, add 0.04ml of 4-chloromethylstyrene (halogen-containing styrene compound) and 7ml of isoprene monomer, continue to react for 1h, repeat this operation 6 times until the reaction is completed. The specific synthetic route is shown in Figure 1 After the temperature drops to room temperature, 6 ml of an isopropanol solution containing 3 wt.% of 2,6-di-tert-butyl-p-cresol is added to terminate the reaction. After isopropanol precipitation, washing, filtration, and vacuum drying, a highly adhesive dendritic branched polymer (branched polymer I) is prepared.

[0041] The molecular weight of branched polymer I was measured by gel permeation chromatography (GPC) of Malvern Company, and the weight average molecular weight of branched polymer I was 57230. w / M n It is 2.688.

[0042] The microstructure of branched polymer I was analyzed by nuclear magnetic resonance (see Figure 2 ), the 1,2-structure polyisoprene content is 5.21%, the 3,4-structure polyisoprene content is 59.27%, the cis-1,4-structure polyisoprene content is 13.33%, the trans-1,4-structure polyisoprene content is 21.50%, and the styrene structure content is 0.68%. The synthesized branched polymer I was subjected to rheological frequency scanning, with a specific test thickness of 1 mm, and a 25 mm plate was used to perform a frequency scanning test from 0.01 Hz to 100 Hz on the sample (see Figure 3 ).

[0043] The adhesion performance of the synthesized branched polymer I was tested using a stainless steel probe (probe diameter of 12 mm, surface roughness Ra of 0.12 um, sample thickness of 1 mm) at different molecular speeds. The relationship between the maximum separation force of the probe and the speed at different separation speeds is shown in the figure below. Figure 4 When the probe separation speed is 5 mm / s, the maximum separation force during the separation process is as high as 40 N.

[0044] The structure of the synthesized branched polymer I is shown in Figure 5 ,from Figure 5 It can be seen that the branched polymer I is dendritic.

[0045] Comparative Example 1:

[0046] Into an 850 ml reaction bottle pre-treated with nitrogen positive pressure, 400 ml of n-hexane solution and 60 ml of isoprene monomer were introduced with a double-ended needle, and 0.71 ml of calibrated n-butyl lithium (molar concentration of 1 mmol / ml) was added to initiate polymerization. The reaction was allowed to proceed in a 60°C water bath for 2 h. After precipitation, washing and drying, the prepared polymer (linear polyisoprene) had a weight average molecular weight of 61860, M w / M n The linear polyisoprene with the same molecular weight has very low viscosity and easily undergoes viscous flow, so that the probe adhesion test cannot be performed.

[0047] Example 2: The highly adhesive dendritic branched polymer was prepared by the following synthesis method:

[0048] In a 850ml reaction bottle pre-treated with nitrogen positive pressure, 400ml of n-hexane solution and 8ml of isoprene monomer were introduced with a double-ended needle, and 1.08ml of calibrated n-butyl lithium (molar concentration of 1mmol / ml) was added to initiate polymerization, and 2,2-di(2-furyl)propane corresponding to half the molar number of n-butyl lithium was added. After reacting in a 60℃ water bath for 2h, 0.02ml of 4-chloromethylstyrene and 7ml of isoprene monomer were added, and the reaction continued for 1h. This operation was repeated 6 times until the reaction was completed. The specific synthetic route is shown in Figure 1 After the temperature drops to room temperature, 6 ml of isopropanol solution containing 3 wt.% of 2,6-di-tert-butyl-p-cresol is added to terminate the reaction. After isopropanol precipitation, washing, filtration, and vacuum drying, the final sample (branched polymer II) is obtained. The molecular weight of the branched polymer II is measured by a gel permeation chromatograph (GPC) of Malvern Company. The weight average molecular weight of M w / M n It is 1.930.

[0049] The microstructure of branched polymer II was analyzed by nuclear magnetic resonance (see Figure 6 ), 1,2-structure polyisoprene content is 2.86%, 3,4-structure polyisoprene is 49.79%, cis-1,4-structure polyisoprene content is 23.10%, trans-1,4-structure polyisoprene content is 23.97%, and styrene-structure polyisoprene is 0.28%. The synthesized polymer was subjected to rheological frequency scanning, with a specific test thickness of 1 mm, and a 25 mm plate was used to perform a frequency scanning test from 0.01 Hz to 100 Hz on the sample (see Figure 7 ).

[0050] The structure of the synthesized branched polymer II is shown in Fig. 9 ,from Fig. 9It can be seen that the branched polymer II is dendritic.

[0051] Comparative Example 2:

[0052] In a 850ml reaction bottle filled with nitrogen positive pressure, 400ml of n-hexane solution and 90ml of isoprene monomer were introduced with a double-ended needle, and 0.61ml of n-butyl lithium (molar concentration of 1mmol / ml) was added to initiate polymerization. After reacting in a 60℃ water bath for 2h, linear polyisoprene was prepared. Finally, it was terminated with isopropanol, precipitated and washed, filtered, and vacuum dried. The molecular weight was measured by Malvern's gel permeation chromatography (GPC). The weight average molecular weight of the linear polymer was 98900, M w / M n is 1.180.

[0053] The synthetic branched polymer II and the linear polymer in comparative example 2 were respectively tested for adhesion by a stainless steel probe (probe diameter of 12 mm, surface roughness Ra of 0.12 μm, sample thickness of 1 mm), and their adhesion properties were tested at different molecular speeds. The relationship between the maximum separation force of the probe and the speed at different separation speeds is shown in the figure below: Figure 8 As shown. Figure 8 It can be seen that the adhesion performance of branched polymers is significantly higher than that of linear polymers with the same molecular weight. When the probe separation speed is 5 mm / s, the maximum separation force during the separation process increases directly from 43 N to 54 N.

[0054] Example 3: The highly adhesive dendritic branched polymer was prepared by the following synthesis method:

[0055] In a 850ml reaction bottle pre-treated with nitrogen positive pressure, 400ml of n-hexane solution and 8ml of isoprene monomer were introduced with a double-ended needle, and 0.73ml of calibrated n-butyl lithium (molar concentration of 1mmol / ml) was added to initiate polymerization, and 2,2-di(2-furyl)propane corresponding to half the molar number of n-butyl lithium was added. After reacting in a 60℃ water bath for 2h, 0.015ml of 4-chloromethylstyrene and 7ml of isoprene monomer were added, and the reaction continued for 1h. This operation was repeated 7 times until the reaction was completed. The specific synthetic route is shown in Figure 1 After the temperature drops to room temperature, 6 ml of isopropanol solution containing 3 wt.% of 2,6-di-tert-butyl-p-cresol is added to terminate the reaction. After isopropanol precipitation, washing, filtration, and vacuum drying, the final sample (branched polymer III) is obtained. The molecular weight of the polymer is measured by a gel permeation chromatograph (GPC) of Malvern Company. The weight average molecular weight of the polymer is 137480, M w / M nIt is 2.070.

[0056] The synthesized polymer was subjected to rheological frequency scanning. The specific test thickness was 1 mm, and the sample was subjected to frequency scanning test from 0.01 Hz to 100 Hz using a 25 mm plate (see Fig.10 ). Through the stainless steel probe adhesion test, it was found that the synthesized branched polymer III has good adhesion behavior and is very suitable for increasing the adhesion performance of polymers.

[0057] Example 4: The highly adhesive dendritic branched polymer was prepared by the following synthesis method:

[0058] In a 850ml reaction bottle pre-treated with nitrogen positive pressure, use a double-ended needle to introduce 400ml of pentane solution and 8ml of styrene monomer, add 1.56ml of calibrated isobutyl lithium (molar concentration is 1mmol / ml) to initiate polymerization, and add 2,2-di(2-furyl)propane corresponding to half the molar number of isobutyl lithium. After reacting in a 68℃ water bath for 1.5h, add 0.04ml of 2-bromostyrene and 7ml of styrene monomer, continue to react for 1h, repeat this operation 5 times until the reaction is completed. When it cools to room temperature, add 7ml of isopropanol solution containing 3wt.% of phenol-free phosphite to terminate the reaction. After isopropanol precipitation, washing, filtration, and vacuum drying, a highly adhesive dendritic branched polymer is prepared.

[0059] Example 5: The highly adhesive dendritic branched polymer was prepared by the following synthesis method:

[0060] In a 850ml reaction bottle pre-treated with nitrogen positive pressure, 400ml of pentane solution and 8ml of 1-phenyl-1,3-butadiene monomer were introduced with a double-ended needle, and 2.40ml of calibrated lithium amide (molar concentration of 1mmol / ml) was added to initiate polymerization, and 2,2-di(2-furyl)propane corresponding to half the molar number of lithium amide was added. After reacting in a 40℃ water bath for 2h, 0.04ml of 4-chloromethylstyrene and 7ml of 1-phenyl-1,3-butadiene monomer were added, and the reaction continued for 1h. This operation was repeated 4 times until the reaction was completed. When the temperature dropped to room temperature, 6ml of isopropanol solution containing 3wt.% of 2,6-di-tert-butyl-p-cresol was added to terminate the reaction. After isopropanol precipitation, washing, filtration, and vacuum drying, a highly adhesive dendritic branched polymer was prepared.

[0061] Example 6: The highly adhesive dendritic branched polymer was prepared by the following synthesis method:

[0062] In a 10L reactor, 4000g of cyclopentane and 60g of butadiene monomer were added, and under the action of 2,2-di(2-furyl)propane (OOPS, the ratio of the amount of OOPS to the initiator at this stage was 1:2), 12mmol of n-butyl lithium was added to initiate polymerization, and the entire reaction system was reacted at 60°C for 2h, with continuous stirring in the middle. After the reaction was completed, 2mmol of 4-chloromethylstyrene was added, and 60g of butadiene monomer was added to react for 1h, and the operation was repeated 6 times. The subsequent operation was the same as in Example 3, and a branched structure polymer with high adhesion performance was obtained, which can significantly improve the adhesion behavior of rubber.

[0063] As can be seen from the above, the highly adhesive dendritic branched polymer synthesized according to the synthesis method of the present invention has excellent adhesive properties and can be used in plastic or rubber blending, which is beneficial to improving the adhesive properties of polymers. In addition, the method has mild operating conditions and is easy to industrialize; or it can be directly used or added to other polymers, which can also significantly improve the bonding properties between objects.

[0064] The above technical features constitute the embodiments of the present invention, which have strong adaptability and implementation effect. Non-essential technical features can be added or reduced according to actual needs to meet the requirements of different situations.

Claims

1. A method for synthesizing a highly adhesive dendritic branched polymer, characterized in that The following steps are involved: (1) Under anhydrous and oxygen-free conditions, anionic polymerization monomers are added to an organic solvent, polymerization is initiated by an initiator, and a structure regulator is added to first prepare a polymer active chain; (2) adding a small amount of halogen-containing styrene compound to the reaction solution of step (1), and adding anionic polymerization monomer again to continue polymerization; (3) After the reaction is completed, step (2) is repeated multiple times, and finally a terminator and an antioxidant are added, and the precipitate is washed, filtered and vacuum dried to obtain a highly adhesive dendritic branched polymer; Wherein, the structure regulator is 2,2-di(2-furyl)propane, and the amount of 2,2-di(2-furyl)propane added is 0.5 times the molar number of the initiator; The halogen-containing styrene compound is 4-chloromethylstyrene, and the molar ratio of the total amount of the halogen-containing styrene compound added to the amount of the initiator added is 0.1 to 10; The initiator is alkyl lithium or alkali metal alkoxide or alkali metal amide or sodium naphthalene; The anionic polymerizable monomer is one or more of conjugated dienes.

2. The method for synthesizing a highly adhesive dendritic branched polymer according to claim 1, characterized in that The initiator concentration is 0.01 mol / L to 10.00 mol / L.

3. The method for synthesizing a highly adhesive dendritic branched polymer according to claim 2, characterized in that The alkyl lithium is one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium and isobutyl lithium; or / and, the alkali metal amide is sodium amide or lithium amide; or / and, the initiator concentration is 0.01 mol / L to 2 mol / L; or / and, the conjugated dienes are one or more of isoprene and butadiene; or / and, the benzene olefin derivatives are one or more of styrene and 1-phenyl-1,3-butadiene.

4. The method for synthesizing a highly adhesive dendritic branched polymer according to claim 1, 2 or 3, characterized in that In step (1), the organic solvent is selected from one or more linear or cyclic organic solvents; the linear organic solvent is selected from one or more of n-hexane, pentane, heptane and octane; the cyclic organic solvent is selected from a long-chain molecular chain or epoxy hydrocarbon organic solvent, the long-chain molecular chain organic solvent is selected from one or more of cyclohexane, cyclopentane and cycloheptane, and the epoxy hydrocarbon organic solvent is selected from tetrahydrofuran.

5. The method for synthesizing a highly adhesive dendritic branched polymer according to claim 4, characterized in that In step (1), the anionic polymerization reaction is carried out at 10° C. to 80° C. for 1 min to 400 min; and in the polymerization reaction solution, the solid content of the anionic polymerization monomer does not exceed 50%.

6. The method for synthesizing a highly adhesive dendritic branched polymer according to claim 5, characterized in that The conditions of anionic polymerization are 30° C. to 70° C., and the solid content of anionic polymerization monomer in the polymerization reaction liquid is 15%.

7. The method for synthesizing a highly adhesive dendritic branched polymer according to claim 1, 2, 3 or 5, characterized in that In step (3), the terminator is one of carbon dioxide, organic acid, water and isopropanol; or / and the antioxidant is one or more of 2,6-di-tert-butylphenol, ketoamine antioxidants, diphenylamine derivatives, p-phenylenediamine derivatives, 2,6-di-tert-butyl-p-cresol, β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, and phenol-free phosphite.

8. The method for synthesizing a highly adhesive dendritic branched polymer according to claim 7, characterized in that The amount of antioxidant added is 1% to 2% of the mass of the high-adhesion dendritic branched polymer.

9. A highly adhesive dendritic branched polymer obtained by the method for synthesizing a highly adhesive dendritic branched polymer according to any one of claims 1 to 8.

10. Use of the high-adhesion dendritic-like branched polymer according to claim 9 in high-adhesion polymer materials.

Citation Information

Patent Citations

  • Dendritic polymers and convergent method of synthesis

    US6255424B1

  • Branched polyolefin synthesis

    US6518383B1